Electric Drive for an Agricultural Vehicle - A. P. Sporov; D. Yu. Pisarev; A. S. Parakhnich (Сельскохозяйственные машины и технологии, 2021)
Abstract. The authors showed the relevance of creating agricultural machines using an electric drive. (Research purpose) The research objective is to develop an experimental prototype vehicle using an electrical schematic diagram of charge and electric drive control. (Materials and methods) The VAZ 111 Oka car was chosen as an experimental vehicle model with an electric drive, since it has a light weight of 645 kilograms, a simple design and a low cost. Mechanical characteristics of the electric motor were calculated and a frequency converter was chosen to control the electric drive.  Laboratory bench tests were conducted. (Results and discussion)The authors   installed storage batteries to power the electric drive, developed an electrical circuit schematics getting charged from a 220 volt alternating voltage network, and received graphs for the discharge of a 40-storage-battery power supply. (Conclusions) An electrical schematic diagram of charge and electric drive control was developed and implemented on an experimental vehicle model. It was determined that at the electric motor continuous operation with the load current of 1 ampere, the batteries get discharged within 104 minutes;  with the current  load of 2 amperes, they get  discharged within 83 minutes; with 3 amperes – within 65 minutes, and with 5 amperes – within 50 minutes, which is enough to drive around the farm. The authors graphically depicted the dependence of the available capacity level on the voltage, as well as the batteries’ discharge on the time at various load currents. The authors carried out two experimental studies on storage batteries’ charging from alternating voltage with the current of 2 and 3 amperes: in the first case, the charging time was 350 minutes, in the second – 310 minutes. It was found out that when using the developed scheme, the batteries are charged evenly.